Independence, Heterogeneity and Uniqueness in Interaction Games - Robin Mason; Akos Valentinyi (Hungarian Academy of Sciences, Institute of Economics, 2003)
This paper shows that incomplete information and sufficient heterogeneity of players can ensure uniqueness in interaction games. In contrast to recent work on uniqueness in interaction games, we do not require strategic complementarity. There are two parts to the argument. First, if a players signal is sufficiently uninformative of the signals of its opponents (in the sense of the Fisher information of the signal), then the players best response to any strategy profile of its opponents is non-decreasing in its signal. Secondly, a contraction mapping argument shows that sufficient heterogeneity ensures that equilibrium is unique.
Keywords: C72; D82; 330; Co-ordination; Interaction games; Heterogeneity; Unique equilibrium